Stop workplace drama : train your team to have no excuses, no complaints, and no regrets - Chism, Marlene (Wiley, 2011)
Overcome the interpersonal challenges holding your business back Is your workplace riddled with gossip, power struggles, and confusion? Do you seek clarity in your management and cohesiveness in your team? Do you have a personal obstacle affecting your professional success? If so, there is good news-help is on the way. Stop Workplace Drama offers down-to-earth, practical methods to help business owners, entrepreneurs, and private practice professionals maximize success, increase productivity, and improve teamwork and personal performance. Identify "drama" barriers and help your employees break free to experience higher personal effectiveness and increased productivity Each of the eight points is full of universal and practical principles any business leader, sales director or entrepreneur can put to use immediately Author Marlene Chism has shared her signature process with organizations such as McDonalds and NASA When you're in the thick of business competition, you and your team need to function freely without internal conflicts, confusions, or rivalries. Stop Workplace Drama ensures that your employees will be able to give their best to create a healthy, profitable workplace